Body size dissatisfaction among young Chinese children in Hong Kong: a cross-sectional study. Issue 6 (20th May 2014) - Knowles, Gemma; Ling, Fiona Chun Man; Thomas, G Neil; Adab, Peymane; McManus, Alison M
Abstract: Objective: To determine the potential predictors of body size dissatisfaction in Chinese children. Design: The Child's Body Image Scale was used to assess body size perception and dissatisfaction. BMI was calculated from objectively measured height and weight. Predictors of body size dissatisfaction were examined by logistic regression analysis. Setting: Hong Kong, China. Subjects: Six hundred and twenty children (53 % boys, aged 6·1–12·9 years) from a state-run primary school. Results: Female sex (adjusted OR (AOR)=1·91; 95 % CI 1·32, 2·76), age (AOR=2·62; 95 % CI 1·65, 4·16 for 8–10 years; AOR=2·16; 95 % CI 1·38, 3·38 for >10 years), overweight (AOR=6·23; 95 % CI 3·66, 10·60) and obesity (AOR=19·04; 95 % CI 5·64, 64·32) were positively associated with desire to be thinner. Size misperception was a strong predictor of body size dissatisfaction, irrespective of actual weight status (AOR=1·90; 95 % CI 1·02, 3·54 for overestimation; AOR=0·43; 95 % CI 0·27, 0·67 for underestimation). Conclusions: Body size dissatisfaction is prevalent among Chinese children as young as 6 years. Female sex, age, overweight, obesity and overestimation of size were associated with increased desire to be thinner. These findings emphasise the importance of preventing body image issues from an early age.